Phosphorus Availability in Differently-Aged Growing Media within a Lebak Swamp Floating Agriculture System - Akhmad Rizalli Saidy; Abdul Haris; Setya Hadi Purnama (Jurnal Ilmu Pertanian Indonesia, 2026)
Floating agriculture, which utilizes local vegetation as a growing medium, is an adaptive innovation that enables year-round crop cultivation in the waterlogged conditions of lowland swamp ecosystems. However, the long-term capacity of these organic media to supply phosphorus (P), a critical nutrient, remains inadequately quantified. This study evaluated the phosphorus-supplying capacity of growing media of different ages (1 and 4 years) derived from identical vegetation sources. Media samples were collected from a 0–20 cm depth in two distinct cultivation systems: one year old media used for mustard greens (Brassica juncea L.) and four year old media used for eggplant (Solanum melongena L.). Analysis of chemical parameters (pH, available P, total P, and organic C) revealed that although the one year old media exhibited a higher pH (4.73–6.84) than the four year old media (4.34–6.05), available phosphorus showed no significant difference between them (1-year: 5.62–28.90 mg kg⁻¹; 4-year: 6.00–24.46 mg kg⁻¹). This indicates that the availability of phosphorus in these organic substrates is less strongly governed by pH than in mineral soils, which is in contrast to established mechanisms. Furthermore, the four year old media contained significantly higher levels of total P (158–1451 mg kg⁻¹) and organic C (29.7-–5.6 g kg⁻¹) than the one year old media (total P: 137–703 mg kg⁻¹; organic C: 4.7–29.7 g kg⁻¹). These findings demonstrate that local vegetation-based growing media in floating agriculture systems possess a sustainable capacity for phosphorus supply, supporting the long-term viability of this cultivation approach in lowland swamp environments. Keywords: floating farming system, lowland swamp, microbial decomposition, phosphatase, planting media age